2022
DOI: 10.3390/cells11233824
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of HGF/VEGF Gene Therapy for Limb Ischemia in Mice with Impaired Glucose Tolerance: Shift from Angiogenesis to Axonal Growth and Oxidative Potential in Skeletal Muscle

Abstract: Background: Combined non-viral gene therapy (GT) of ischemia and cardiovascular disease is a promising tool for potential clinical translation. In previous studies our group has developed combined gene therapy by vascular endothelial growth factor 165 (VEGF165) + hepatocyte growth factor (HGF). Our recent works have demonstrated that a bicistronic pDNA that carries both human HGF and VEGF165 coding sequences has a potential for clinical application in peripheral artery disease (PAD). The present study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A study in diabetic db/db mice suggests that factors produced in myofibers act upon endothelial cells to modulate their gene expression and function ( 66 ). In high fat diet-fed mice with impaired glucose tolerance and HLI surgery, exogenous expression of hepatocyte growth factor and vascular endothelial growth factor 165 improved muscle regeneration by improving innervation and muscle regeneration ( 67 ). Studies in our laboratory have shown that following HLI the extent of skeletal muscle injury is more severe in diabetic mice (HFD) compared to non-diabetic and this was associated with a higher rates of limb amputation and poor skeletal muscle function ( 64 ).…”
Section: Adaptations Associated With Padmentioning
confidence: 99%
“…A study in diabetic db/db mice suggests that factors produced in myofibers act upon endothelial cells to modulate their gene expression and function ( 66 ). In high fat diet-fed mice with impaired glucose tolerance and HLI surgery, exogenous expression of hepatocyte growth factor and vascular endothelial growth factor 165 improved muscle regeneration by improving innervation and muscle regeneration ( 67 ). Studies in our laboratory have shown that following HLI the extent of skeletal muscle injury is more severe in diabetic mice (HFD) compared to non-diabetic and this was associated with a higher rates of limb amputation and poor skeletal muscle function ( 64 ).…”
Section: Adaptations Associated With Padmentioning
confidence: 99%